2015
DOI: 10.1111/eva.12289
|View full text |Cite
|
Sign up to set email alerts
|

Do stressful conditions make adaptation difficult? Guppies in the oil‐polluted environments of southern Trinidad

Abstract: The ability of populations to rapidly adapt to new environments will determine their future in an increasingly human-modified world. Although meta-analyses do frequently uncover signatures of local adaptation, they also reveal many exceptions. We suggest that particular constraints on local adaptation might arise when organisms are exposed to novel stressors, such as anthropogenic pollution. To inform this possibility, we studied the extent to which guppies (Poecilia reticulata) show local adaptation to oil po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 130 publications
(224 reference statements)
0
31
0
Order By: Relevance
“…No differences in survival and growth were found over a 6-day period. However, guppies from an unpolluted river in the north had a small, but significant, reduction in survival and growth in the polluted river [27]. The small difference in survival in that study provided little evidence for adaptation.…”
Section: The Trinidad Guppy (Poecilia Reticulata) As a Model To Studymentioning
confidence: 82%
See 1 more Smart Citation
“…No differences in survival and growth were found over a 6-day period. However, guppies from an unpolluted river in the north had a small, but significant, reduction in survival and growth in the polluted river [27]. The small difference in survival in that study provided little evidence for adaptation.…”
Section: The Trinidad Guppy (Poecilia Reticulata) As a Model To Studymentioning
confidence: 82%
“…
Figure 1.Distribution of alleles for a DNA microsatellite within the CYP1A gene for guppies living in four rivers in Trinidad. The Vance and Morne rivers are unconnected by freshwater and have stretches that are heavily contaminated with crude oil, described in [27]. Within each polluted river, data are pooled for populations from unpolluted and polluted stretches as no frequency differences were observed.
…”
Section: The Trinidad Guppy (Poecilia Reticulata) As a Model To Studymentioning
confidence: 99%
“…However, local adaptation to pollution may be weak if chronic stress levels lead to small populations and/or there is high gene flow between different sites (Rolshausen et al. ), which may be the case in the stream ecosystems we studied. Although it is highly likely that both ecological and evolutionary processes determine community structure, we cannot disentangle these factors as we only assessed structural differences in communities, not phenotypic or genetic changes in responding taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The selection experiments in this study used similar approaches as prior studies, with similar starting population size (hundreds of copepods). Difficulties in inducing an evolutionary response to crude oil was also found in populations of Trinidad guppies, where populations from oil‐polluted tributaries showed little evidence of local adaptation in survival and growth (Rolshausen et al., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In an older study, imposing crude oil exposure for 2–10 days in marine gastropods revealed allele frequency shifts at two allozyme loci, suggesting an evolutionary response to crude oil, though the functional implications of these allele frequency shifts are unclear (Nevo & Lavie, 1989). In a comparison between populations of the Trinidad guppy Poecilia reticulate in oil‐polluted versus unpolluted streams, populations in oil‐polluted habitats showed little evidence for adaptation to oil pollution, but were actually maladapted to their local environment (Rolshausen et al., 2015). An intriguing comparative study found that the Gulf killifish Fundulus grandis at an oil‐contaminated site in the Gulf of Mexico exhibited changes in genome expression and larval CYP1A enzyme expression (a biomarker for PAH exposure) that was divergent from fish from uncontaminated sites, 1–4 months after the oil spill (Whitehead, Dubansky, et al.…”
Section: Introductionmentioning
confidence: 99%